2000
DOI: 10.1128/iai.68.4.2102-2109.2000
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Exogenous T-cell Epitopes to the 19-Kilodalton Region ofPlasmodium yoeliiMerozoite Surface Protein 1 (MSP119) Can Enhance Protective Immunity against Malaria and Modulate the Immunoglobulin Subclass Response to MSP119

Abstract: The degree of protection against Plasmodium yoeliiasexual blood stages induced by immunization of mice with the 19-kDa region of merozoite surface protein 1 (MSP119) is H-2 dependent. As a strategy to improve the protection, mouse strains with disparate H-2 haplotypes were immunized with glutathioneS-transferase (GST)–MSP119 proteins including either a universal T-cell epitope from tetanus toxin (P2) or an I-Ak-restricted T-cell epitope (P8) fromPlasmodium falciparum Pf332. In H-2k mice which are poorly protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 65 publications
8
37
0
Order By: Relevance
“…Its capacity to elicit and restimulate native antigenspecific CD4 + helper T cells may nevertheless mean that co-administration of the unstructured antigen alongside native MSP1 19 may accordingly improve the 'quality' of the T cell response in a way that would lead to faster development of higher native protein-specific antibody titers. Earlier observations have shown that the inclusion of specific T cell epitopes together with the folded protein can boost antibody responses in a rodent model of malaria [41]. Our data here suggest that coadministration of R/A and native antigen influences the antibody response to the native protein.…”
Section: Discussionsupporting
confidence: 63%
“…Its capacity to elicit and restimulate native antigenspecific CD4 + helper T cells may nevertheless mean that co-administration of the unstructured antigen alongside native MSP1 19 may accordingly improve the 'quality' of the T cell response in a way that would lead to faster development of higher native protein-specific antibody titers. Earlier observations have shown that the inclusion of specific T cell epitopes together with the folded protein can boost antibody responses in a rodent model of malaria [41]. Our data here suggest that coadministration of R/A and native antigen influences the antibody response to the native protein.…”
Section: Discussionsupporting
confidence: 63%
“…This reduction in parasite burden would allow the recipient of the vaccine to survive the infection and give the recipient time to develop additional parasite-specific immune responses independent of the vaccine (14). The results presented here expand upon a previous study that expressed a GST fusion protein containing MSP1 19 with a defined T-cell epitope inserted between GST and MSP1 19 (1).…”
Section: Discussionsupporting
confidence: 59%
“…A number of studies have focused on the use of universal helper T-cell epitopes to provide help for B cells, thereby enhancing the immunogenicity of small-subunit-based vaccines (1,17,24). While conjugating B-cell epitopes (haptens) to proteins is a more classical approach to providing T-cell help (21) and one that would result in immunological responsiveness among a greater proportion of the population, some studies have suggested that prior exposure to the protein can result in a diminished response to the hapten following protein-hapten immunization (8,11,23,(26)(27)(28).…”
mentioning
confidence: 99%
“…In particular, human IgG3 shares many features with mouse IgG2b. Both human IgG3 and mouse IgG2b are minor components of normal serum, bind with high affinity to Fc receptor, fix complement, are preferentially induced during Th1 immune responses, and are especially effective at mediating immunity to blood stage malaria infection (1,8,18,23,48,50,51). These observations, together with accumulating evidence that the machinery for class switch recombination is conserved between humans and mice (27), suggest that there may also be conservation of the signals required for initiation of specific Ig isotype and subclass switching and thus that information derived from mouse models may be directly applicable to studies of human B cells.…”
Section: Discussionmentioning
confidence: 99%